Selection indexes and principal components for agronomic and bromatological traits in forage cactus - Jesus, Mariana Santos de (2022)
The objective of the present work was to compare selection indexes focused on the selection of forage cactus (Opuntia ficus-indica) accessions at initial generations. Sixty-five accessions from different locations in the semiarid region of the state of Bahia, Brazil, were evaluated in a randomized complete block design with three replications. Agronomic and bromatological traits were evaluated. The genetic parameters were predicted by using mixed models (REML/BLUP). The linear correlation degree between variables was estimated through Pearson's correlation analysis. Selection gains were predicted using four selection indexes: Smith-Hazel index, with two combinations of economic weights; rank sum index of Mulamba and Mock; and Elston's multiplicative index. The selection intensity applied was 30%, which allowed the selection of the 20 best accessions. The analysis of deviance showed significant effect for all traits. The estimate of genetic parameters evidenced the existence of genetic variability for the O. ficus-indica accessions. The Smith-Hazel index (combination 1) was important for primary (fresh weight and cladode dry weight) and bromatological traits (acid detergent fiber and neutral detergent fiber), expressing higher selection gains than the other indexes. The rank sum and multiplicative indexes resulted in selection gains for most evaluated traits. The results of accessions 2, 4, 5, 7, 9, 11, 14, 15, 18, 26, 27, 34, 37, 38, 39, 41, 45, 49, 51, 52, 53, and 58 were promising for their inclusion in breeding programs, as they were selected by at least two of the four selection indexes used.